The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7554/elife.28199
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for SUN5 in anchoring sperm head to the tail

Abstract: SUN (Sad1 and UNC84 domain containing)-domain proteins are reported to reside on the nuclear membrane playing distinct roles in nuclear dynamics. SUN5 is a new member of the SUN family, with little knowledge regarding its function. Here, we generated Sun5−/− mice and found that male mice were infertile. Most Sun5-null spermatozoa displayed a globozoospermia-like phenotype but they were actually acephalic spermatozoa. Additional studies revealed that SUN5 was located in the neck of the spermatozoa, anchoring sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
99
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 59 publications
(71 reference statements)
2
99
0
1
Order By: Relevance
“…Deletion of SUN5 did not impact the formation of HTCA, but HTCA was separated from implantation fossa at the beginning of sperm deformation, resulting in acephalic spermatozoa. 23,29 Zhu et al reported that 72.00% (18/25) of their acephalic spermatozoa cohort is caused by SUN5 and PMFBP1 mutations, suggesting that other gene mutations are also involved in the development of acephalic spermatozoa. 16 In previous studies, we have reported that the mutations in SUN5, TSGA10 and BRDT may result in acephalic spermatozoa in human.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of SUN5 did not impact the formation of HTCA, but HTCA was separated from implantation fossa at the beginning of sperm deformation, resulting in acephalic spermatozoa. 23,29 Zhu et al reported that 72.00% (18/25) of their acephalic spermatozoa cohort is caused by SUN5 and PMFBP1 mutations, suggesting that other gene mutations are also involved in the development of acephalic spermatozoa. 16 In previous studies, we have reported that the mutations in SUN5, TSGA10 and BRDT may result in acephalic spermatozoa in human.…”
Section: Discussionmentioning
confidence: 99%
“…Rapgef6‐KO mice have small, atrophied, hypospermatogenic testes, and their epididymal sperm have low‐motility with inhibited fertilizing ability (K. Okada et al, ). Sun5 anchors sperm head to the tail and Sun −/− male mice are infertile with sperm having heads separated from tails and without chromatin and acrosome (Y. Shang et al, ). On the other hand, Setd2 (SET domain–containing 2) is the major histone methyltransferase that has important function in embryonic stem cell differentiation and in spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…. Sun5 anchors sperm head to the tail and Sun −/− male mice are infertile with sperm having heads separated from tails and without chromatin and acrosome (Y Shang et al, 2017)…”
mentioning
confidence: 99%
“…Furthermore, there is growing evidence that mutations in human genes encoding NE proteins can have deleterious effects on the development of fertilization‐competent spermatozoa and lead to severe infertility phenotypes in men (Zhu et al ., , ). A correlation between spermatogenesis‐specific NE dynamics and male fertility is also supported by several knockout mouse models (Alsheimer et al ., ; Ding et al ., ; Pierre et al ., ; Horn et al ., ; Link et al ., ; Pasch et al ., ; Chen et al ., ; Shang et al ., ). Despite considerable advances in the field, an integrative analysis of the available scientific data regarding the involvement of NE proteins in the successful progression of male meiosis and spermiogenesis has never been presented.…”
Section: Introductionmentioning
confidence: 97%
“…In recent decades, numerous studies have demonstrated that spermatogenesis requires extensive rearrangement of the NE network, including the composition of its specific proteome and the localization of these proteins. Interestingly, the list of NE proteins restricted to or highly enriched in mammalian male germline cells is rapidly increasing, comprising a total of 10 NE components at present (Furukawa, Inagaki & Hotta, ; Schutz et al ., ; Gob et al ., ; Morimoto et al ., ; Pierre et al ., ; Pasch et al ., ; Chen et al ., ; Shang et al ., ; Elkhatib et al ., ). Furthermore, there is growing evidence that mutations in human genes encoding NE proteins can have deleterious effects on the development of fertilization‐competent spermatozoa and lead to severe infertility phenotypes in men (Zhu et al ., , ).…”
Section: Introductionmentioning
confidence: 99%